Conceptual aspects of a liver transplant program in Uruguay - Ruso, Luis; Balboa, Oscar (Cirugía del Uruguay, 1996)
increasing indication and encouraging results. The present impossibility of offering this therapeutical option to carriers of terminal hepatopaty is a serious gap in health care which should be briefly modified. The aim of this paper es to analyse conceptual aspects as regards material, legal and economical resources which are a basis far discussion of a project far the developement of a hepatic transplantation program in Uruguay. The authors consider it absolutely necessary to count on a highly complex facilities hospital, a multiapproach team with adequate technical capacity and an efficient program of organ obten/ion. Besides, the features and dimension of the programa require a thorogh economical analysis. The creation of a multiapproach team so as to analyse the feasability of carrying out hepatic transplantation in our country is proposed.